Prevalence difference of Helicobacter pylori infection between Tibetan and Han ethnics: The protocol of a meta-analysis on epidemiologic studies - Bai, Dan (Medicine (Baltimore), 2019)
OBJECTIVES: Helicobacter pylori (Hp) is an identified carcinogenic pathogen of human gastric cancer. China is not only one of the countries with high incidence and mortality of gastric cancer, but also a high infection area of Hp. As a multi-ethnic country, China may have a diverse prevalence of Hp infection among ethnics. This meta-analysis tends to compare the prevalence of Hp infection between Tibetan and Han ethnics, the results may provide evidence for targeted screening and eradication of Hp in China. METHODS: The following databases will be searched: PubMed, Web of Science, Technology Periodical Database (VIP), China National Knowledge infrastructure (CNKI), and WanFang databases. Studies which reported the prevalence of Hp infection between Tibetans and Hans in China are eligible. Two reviewers will independently screen studies, extract data and assess the risk of bias of included studies. The prevalence of Hp infection between Tibetan and Han ethnics will be compared by meta-analysis. Heterogeneity tests and meta-analyses will be conducted using RevMan 5.3 and Stata 12.0 softwares. Meanwhile, subgroup analysis, publication bias and sensitivity analysis evaluation will be performed where applicable. RESULTS: This study will be reported in compliance with the PRISMA statement. This systematic review will not be submitted for any ethical approval since no privacy health information will be included. The findings will be published through peer-reviewed publications or conference presentations. PROSPERO REGISTRATION NUMBER: CRD42019121192. CONCLUSIONS: Our study will provide us evidence for tailored strategy and robustness of Hp screening and eradication among Tibetans.